Amberboa maroofii (Asteraceae, Cardueae–Centaureinae), a new species from Kurdistan, Iran - Negaresh, Kazem (Phytotaxa, 2015)
Amberboa maroofii is described and illustrated as a new species from Kurdistan Province, W Iran. It is a diploid species (2n = 2x = 32) and morphologically most similar to A. glauca. The new species is also compared with A. moschata, A. sosnovskyi and A. zanjanica. Its distribution range covers a small area; it grows on clay at elevations of 1400–1800 m.